Strategic tourism planning in Portugal : challenges for the national tourism development - Bailoa, Sandra (Array, 2020)
The growth of tourism in Portugal allowed leveraging the economy on the last decade more than any other economic activity. The positive results in many indicators, such as the contribution to GDP, exports and revenues, show that it has been considered an engine of the economy that has produced effects in all the regions of the country. Also contributing to these results were the various strategies that the government has continually defined over the past two decades. This paper starts with a brief literature review and presents a descriptive analysis of the main long-term instruments that feature the Portuguese strategy for tourism, showing the important role that planning can have on the management of the impacts that come from the implementation of these activities. Also, the results of the main indicators (published by several different sources) are presented. The results reveal that there are still several issues that need addressing, so the main challenges for tourism development in Portugal are exposed.